2015
DOI: 10.1111/jre.12329
|View full text |Cite
|
Sign up to set email alerts
|

The histopathological and morphometric investigation of the effects of systemically administered humic acid on alveolar bone loss in ligature‐induced periodontitis in rats

Abstract: Within the limits of this study, it can be suggested that humic acid, when administered systemically as an 80 mg/kg dose, may prevent alveolar bone loss and reduce inflammation in the rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
0
16
0
4
Order By: Relevance
“…Humic acid was obtained from peat coming from the western Black Sea region and was diluted in sterile saline solution to reach the study concentrations (80 mg/kg) [ 20 ]. The concentration of the trace elements in the humic acid solution such as Si, Se, Ca, Mg, Fe, and Zn is provided in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Humic acid was obtained from peat coming from the western Black Sea region and was diluted in sterile saline solution to reach the study concentrations (80 mg/kg) [ 20 ]. The concentration of the trace elements in the humic acid solution such as Si, Se, Ca, Mg, Fe, and Zn is provided in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In the oral cavity, we have previously shown that humic acid prevents alveolar bone loss and reduce inflammation in rats [ 20 ]. In addition, carbohydrate-derived fulvic acid, which is a major constituent of humic acids, has been shown to have a broad-spectrum antimicrobial activity against orally active microorganisms [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ionel and Lucaciu 2015, Çalışır et al, 2016 comes in aggrement with our result, they found that PD in rats after 4 weeks revealed pronounced inflammation of PDL and advanced resorption of the alveolar bone crest. [21][22] While after 4 weeks, the same group showed irregular areas of external root resorption with the destruction of periodontal ligament fibers and massive inflammation. hasan and palmer 2016 aggremented with our results.…”
mentioning
confidence: 99%
“…The ligature‐induced periodontitis model was used because it mimics features of human periodontitis, including the formation of an inflammatory infiltrate, loss of attachment, and loss of alveolar bone. The majority of studies have kept the ligature in place from 15 to 60 days for the induction of periodontal destruction (Çalışır, Akpınar, Poyraz, Göze, & Çınar, ; de Molon et al, ; Fontana, Kurachi, Mendonça, & Bagnato, ; Johnson, ). In this study, ligatures were removed 27 days after their placement.…”
Section: Discussionmentioning
confidence: 99%